The genus Cyphoderopsis Carpenter (Collembola: Paronellidae) in Thailand and a faunal transition at the Isthmus of Kra in Troglopedetinae - Jantarit, Sopark; Satasook, Chutamas; Deharveng, Louis (Zootaxa, 2013)
The genus Cyphoderopsis Carpenter is recorded for the first time from continental Southeast Asia, with four new species described from Peninsular Thailand. New characters of taxonomic importance are introduced. The new species herein described are distinguished from other species of the genus by the following combination of characters: dens with two rows of spines, absence of eyes and pigment, and claw with inner teeth. They differ among them in the number of inner teeth on claw, morphology of tenent hairs (pointed versus clavate), number of dental spines and number of central macrochaetae on Th.II (3+3 versus 4+4). The genus Cyphoderopsis in Thailand is shown to be restricted to the South of the Isthmus of Kra, while the closely related genus, Troglopedetes Absolon, replaces it further north, providing new evidence that the Isthmus of Kra is an important biogeographical boundary in Southeast Asia. A checklist and a key to world species of the genus are given.